2021
DOI: 10.3390/en14186003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of the R744/R404A Cascade Refrigeration System with Internal Heat Exchanger. Part 1: Coefficient of Performance Characteristics

Abstract: This study evaluates the performance of an R744/R404A cascade refrigeration system (CRS) with internal heat exchangers (IHE) in supermarkets. R744 is used as the refrigerant in a low-temperature cycle, and R404A is used as the refrigerant in a high-temperature cycle. In previous studies, there are many studies including theoretical performance analysis of the CRS. However, experimental studies on the CRS are lacking, and experimental research on the R744/R404A system with an IHE is scarce. Therefore, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Figure 2 was designed to analyze the characteristics of the R744/R404A CRS [13]. Additionally, the experimental procedure including the description of the experimental apparatus, the experimental conditions (Table 2), the main components and detailed characteristics of the experiments are the same as in a previous paper [13]. The main components of the experiments are listed in Table 3.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…Figure 2 was designed to analyze the characteristics of the R744/R404A CRS [13]. Additionally, the experimental procedure including the description of the experimental apparatus, the experimental conditions (Table 2), the main components and detailed characteristics of the experiments are the same as in a previous paper [13]. The main components of the experiments are listed in Table 3.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…It has been practically employed and analyzed in vaccine storage task as well by Liu et al [ 34 ]. Some notable contributions to the experimental analysis include the works of S. Cabello et al [ 35 ], Bingming et al [ 36 ], Dopazo and Ferna'ndez-Seara [ 37 ], Sanz-Kock et al [ 38 ], Wang et al [ 39 ] and Jeon [ 40 ]However, for sectors that require ultra-low temperatures, maintaining the corresponding high-pressure ratio is not feasible with a double cascade system. Cascade refrigeration systems with three stages, a relatively recent innovation in this field, could be a cost-effective solution to this problem [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the volumetric efficiency of HTC compressor greatly deteriorated during pull‐down process. Jeon 26 experimentally researched a CRS with refrigerant couple R744‐R404A. They suggested that refrigerant R404A could be replaced by R448A and R449A in CRS.…”
Section: Introductionmentioning
confidence: 99%